1996
DOI: 10.1023/a:1016054623543
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: PDMAEMA is an interesting vector for the design of in vivo and ex vivo gene transfection systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 319 publications
(170 citation statements)
references
References 14 publications
4
165
1
Order By: Relevance
“…[31] The large aggregates of the complexes of DNA and PL were obtained at the C/A ratio of 3, while PtmL allowed the formation of nonaggregating complexes at the same C/A ratio (Figure 3). The quaternary ammonium groups seem to enhance both the electrostatic and sterical repulsion of complexes, and prevent the aggregation of the complexes at the same C/A ratio.…”
Section: Discussionmentioning
confidence: 97%
“…[31] The large aggregates of the complexes of DNA and PL were obtained at the C/A ratio of 3, while PtmL allowed the formation of nonaggregating complexes at the same C/A ratio (Figure 3). The quaternary ammonium groups seem to enhance both the electrostatic and sterical repulsion of complexes, and prevent the aggregation of the complexes at the same C/A ratio.…”
Section: Discussionmentioning
confidence: 97%
“…Since positively charged complexes interact with the cell surface through an electrostatic interaction with anionic substances on the cell surface, internalization events are affected by the zeta-potential of the polyplexes. It has been reported that polyplexes composed of polycations with MWs of several thousands exhibit high zeta-potentials [13,[26][27][28][29][30], irrespective of the polycations used. PK and PR are known to form polyplexes with pDNA in a different manner [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it can be concluded that cellular uptake occurs on 293T cells since luciferase was detected after transfection with p(DMAPEMA) complexes in the presence of endosome disruptive agent (chloroquine). [3] The performances of three polymers (Exgen 500, p(DMAEMA) and p(DMAPEMA)) were confirmed by transfection with a pEGFP plasmid on BHK21 cells and analysis by flow cytometry. This method is more straightforward for determining transfection efficiency.…”
Section: In Vitro Transfection Studiesmentioning
confidence: 95%
“…The hydrolysis ratio of the polymers was determined by integration of 1 H NMR spectra ( Figure 2). The integral between 3.6 and 4.5 ppm, corresponding to the protons H4 (3) , H5 (3) , H4 0 (4) and H5 0 (4) , was normalized to a value of 4, then this area was split into two regions: 3.6-3.9 ppm (a-alcoholic methylene H5 0 (4) ) and 3.9-4.5 ppm (methylenes H4 (3) , H5 (3) and H4 0 (4) ). The hydrolysis ratio was calculated according to Equation (1).…”
Section: Kinetics Of Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation